Relação entre reflectâncias de imagens orbitais e transporte de sedimentos em suspensão no Rio Doce - Vilches, Thanira Thammy Bastos (2013)
Suspended solids transport excess, caused by erosion, may limit water use and cause rivers siltation. Suspended solids concentration may be assessed by remote sensing because the reflectance of the scenes, in the visible and infrared ranges, is positively influenced. This work aims at the understanding of the variability of suspended sediments concentrations in a Doce river stretch located in Espírito Santo state, Brazil, through spectral analysis of satellite images data and analysis of field measurements results. There were analyzed suspended solids concentrations for samples collected in Regência and Colatina Doce river sections and images captured by LANDSAT 5 TM satellite. To obtain reflectance values, the following operations were performed: geometric correction, conversion of DN values to apparent FRB values, atmospheric correction, using the 6S model (FRB surface), and transformation of NCs values.The results showed that, for the images corrected from atmospheric effects, the values of the ND curve related to the apparent FRB are higher than the values of the surface s FRB curve in the visible region, due to the electromagnetic radiation scattering phenomenon. In the near-infrared regions, the reverse was observed, because of the absorption of electromagnetic radiation by the atmosphere. It was observed positive correlation between reflectance and suspended solids concentration, despite the difficulties in obtaining data from same satellite images and field sample collection dates. For Regência data, the best correlation was obtained for band 1, located in the visible range of the surface s FRB curve, suggesting less suspended sediment transport. For Colatina, the best correlation occurred for band 4, located in the near-infrared range of the same surface s FRB curve, indicating greater sediment transport in this part of the Doce river during the sampling dates. It was concluded that the surface reflectance best represents the water spectral curve and that the correlated data showed the following pattern: smaller reflectance corresponds to lower water suspended solids concentration